John James Beckley family papers - Beckley, John James, 1757-1807.; Beckley, Alfred, 1802-1888.
Correspondence (1791-1829) and memorandum book (1791-1799) of John James Beckley; and correspondence (1829-1849), memorandum books, autobiography (1886), scrapbook, newspaper clipping, and other papers of his son, U.S. Army officer Alfred Beckley. Also includes four books signed by John James Beckley that were part of his library.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Librarian of Congress and clerk of the U.S. House of Representatives.
Collection related to the Library of Congress Archives.
Keywords: Beckley family; Library of Congress; Library of Congress -- Officials and employees; United States. -- Army -- Officers; United States. -- Congress. -- House; United States -- Politics and government -- 1783-1865.; Clerks, U.S. House of Representatives; Librarians of Congress